A cost‐effectiveness analysis of real‐world treatment for elderly patients with multiple myeloma using a full disease model. (7th May 2015) - Blommestein, Hedwig M.; Verelst, Silvia G. R.; de Groot, Saskia; Huijgens, Peter C.; Sonneveld, Pieter; Uyl‐de Groot, Carin A.
Abstract: Objectives: To study the impact of novel treatments for elderly (≥66 yr) patients with multiple myeloma (MM) in daily practice by comparing real‐world effects [overall survival (OS) and quality‐adjusted life years (QALYs)] and costs over time. Also, we calculate cost‐effectiveness of treatment sequences commonly prescribed to predict effects and costs if patients had received a different treatment sequence. Methods: Real‐world data including patient and disease characteristics, treatment information and resource use were collected from 1054 elderly patients with MM. Patients received first‐line treatment during 2004–2007 (cohort 1) and 2008–2013 (cohort 2). The two cohorts were compared using a patient‐level simulation (PLS) model comprising regression models which used patient and disease characteristics to estimate time to next treatment and death. Effects and costs from cohort 2 were compared to 4 commonly prescribed real‐world sequences. Results: Utilisation of novel agents was higher for cohort 2 compared to cohort 1. Modelled average OS for cohort 1 was 38 months (median 25) and total costs €44 200. OS for cohort 2 was 42 months (median 28) and total costs €69 017. The model identified potential OS gains if all patients were to be treated using combinations containing thalidomide, lenalidomide and bortezomib in that particular order. This sequence had, compared to real‐world treatment, the most favourable incremental cost‐effectiveness ratio, €24 618 per life year gained and €34 875 per QALY. Conclusions: Our patient‐level model enabled to study the effects and costs of entire treatment sequences and to compare real‐world treatment patterns over time. Increased utilisation of novel agents improved survival and increased costs for real‐world patients with MM in the Netherlands.